Making rural cities smart – by upgrading existing cities or creating new ones? - Némediné Kollár, Kitti; Topa, Zoltán; Káposzta, József; Borbás, Péter Dániel (Studia Mundi – Economica, 2020)
The importance of SMART initiatives is undeniable nowadays. Due to technological, economic and social processes, our world faces many global challenges, such as food and water shortage, global economic imbalance, demographic problems and – based on the authors’ opinion – vastly underrated global inequality. These problems need to be addressed in the next few decades in order to ensure that we can leave a safe and sustainable planet to our descendants. Since great decisions require long-term planning and analysis, this paper is about taking a look into the possible future of cities by discussing SMART Cities generally, with a special focus on SMART cities built from scratch, to see how they can be the solution of current and future problems. The authors’ reviewed relevant literature to prepare this paper.